NLC-Based Rifampicin Delivery System: Development and Characterization for Improved Drug Performance Against Staphylococcus aureus - Javiera Carrasco-Rojas; Felipe I. Sandoval; Christina M. A. P. Schuh; Carlos F. Lagos; Javier O. Morales; Francisco Arriagada; Andrea C. Ortiz (Pharmaceutics, 2025)
Background/Objectives: Rifampicin is a typical antibiotic used for the treatment of Staphylococcus aureus (S. aureus) infections; however, its clinical utility is limited by poor aqueous solubility, chemical instability, and increasing bacterial resistance. Nanostructured lipid carriers (NLCs) offer a promising strategy to improve drug solubility, stability, and antimicrobial performance. Methods: In this study, rifampicin-loaded NLC (NLC-RIF) was developed using a hot homogenization with a low energy method and characterized in terms of particle size, polydispersity index, zeta potential, encapsulation efficiency, colloidal stability, and drug loading. Results: In vitro release studies under sink conditions demonstrated a biphasic release pattern, best described by the Korsmeyer–Peppas model, suggesting a combination of diffusion and matrix erosion mechanisms. Antimicrobial activity against S. aureus revealed a substantial increase in potency for NLC-RIF, with an IC50 of 0.46 ng/mL, approximately threefold lower than that of free rifampicin. Cytotoxicity assays in HepG2 cells confirmed over 90% cell viability across all tested concentrations. Conclusions: These findings highlight the potential of NLC-RIF as a biocompatible and effective nanocarrier system for enhancing rifampicin delivery and antibacterial activity.